2023
DOI: 10.1155/2023/5570030
|View full text |Cite
|
Sign up to set email alerts
|

Additive Effects of Exercise and Vitamin D Supplementation (with and without Calcium) on Bone Mineral Density in Older Adults: A Systematic Review and Meta-Analysis

Abstract: Exercise is a recognized component in the prevention and therapy of osteoporosis. The present systematic review and meta-analysis aimed to determine the effect of Vitamin D (Vit-D) added to exercise versus exercise alone on bone mineral density (BMD) at the lumbar spine (LS) or hip in older adults. A systematic review based on six literature databases according to PRISMA included (a) exercise trials, with an exercise (EX) and a combined exercise + Vit-D group (EX + Vit-D), (b) intervention ≥ 6 months, and (c) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 49 publications
0
2
0
Order By: Relevance
“…Ca acts by stimulating muscle contraction through its role in actin-myosin cycling, and activating mTOR pathway to stimulate protein synthesis ( 38 ). VD may enhance Ca absorption and bioavailability for optimal muscle effects ( 39 ). VD is a key modulator of the musculoskeletal system, and a study including 4,236 middle-aged and elderly Chinese residents showed that low VD levels were associated with age-related decreases in muscle mass, suggesting that VD supplementation may have a role in improving muscle function ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…Ca acts by stimulating muscle contraction through its role in actin-myosin cycling, and activating mTOR pathway to stimulate protein synthesis ( 38 ). VD may enhance Ca absorption and bioavailability for optimal muscle effects ( 39 ). VD is a key modulator of the musculoskeletal system, and a study including 4,236 middle-aged and elderly Chinese residents showed that low VD levels were associated with age-related decreases in muscle mass, suggesting that VD supplementation may have a role in improving muscle function ( 40 ).…”
Section: Discussionmentioning
confidence: 99%
“…This has been determined in several animal models, but current human trials have shown exercise only provides a partial protection against bone mineral loss and requires supplementation with an anti-resorptive (Sibonga et al, 2019). Pharmacologically, protein, calcium, vitamin D, and high intake of alkaline precursors are shown to reduce bone loss (Hajisadeghi et al, 2021;Fischer et al, 2023).…”
Section: Microgravitymentioning
confidence: 99%